Ethical leadership - Starratt, Robert J. (San Francisco : Jossey-Bass, 2004)
Shows educational leaders how to move beyond mere technical efficiency in the delivery and performance of learning. This work challenges educators to become ethical leaders who understand the learning process as a profoundly moral activity that engages the full humanity of the school community.
Includes bibliographical references and index.
Keywords: Educational leadership -- Moral and ethical aspects -- United States; School administrators -- Professional ethics -- United States; School improvement programs -- United States